Investigation of stud bolts with incorporated fiber bragg grating sensors for real-time flange bolt integrity monitoring - Abdullah, Muhammad; Mohd Hafizi, Zohari; Rosdalilah, Ramli; Nur Ainaa Adhreena, Muhamad Shukri; Priyandoko, Gigih (Semarak Ilmu Publishing, 2026)
This paper introduces an innovative method that uses a stud bolt in conjunction with a Fibre Bragg Grating (FBG) sensor. The current layout makes it easier to measure strain caused by bolt tightening and helps find possible damage caused by too much pressure or load on the flange. This project aims at measuring the axial strain and deflection of M18 stud bolts on a typical flange for pipe connections. This will be accomplished by utilising multiplexed Fibre Bragg Grating (FBG) sensors embedded into the bolts. The flange was subsequently exposed to several point loadings, applied directly in a vertical orientation. The results indicate that an increase in the magnitude of the point load on the flange structure, coupled with a higher tightening torque, results in reduced stress fluctuations on the bolt. The flange structure will be stiff enough to keep stress levels stable at each bolt when the torque is high. This will eliminate the chance of damage during repeated loading conditions.